2014
DOI: 10.3126/jcmc.v3i4.9551
|View full text |Cite
|
Sign up to set email alerts
|

The First Dental Visit

Abstract: Oral health is a vital part of overall infant health. An early dental visit is important in rendering prevention oriented inter­vention and parental counselling regarding the oral health. To assess the age and common chief complaint of the children in their first dental visit. This was a retrospective study done using case records of 842 children, who reported to the Depart­ment of Pedodontics and Preventive Dentistry, chitwan medical college. The age groups were divided into four categories; less than 3 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 2 publications
0
12
1
Order By: Relevance
“…In the present study, only 0.6% of the children were under 1 year of age. An FDV at less than 3 years of age was reported in 3.00-40.50% of the population in previous studies (13,(19)(20)(21), whereas the rate was 5.5% in the present study. Other reports have stated that most of the children were aged between 6 and 9 years (12,19) or 3 and 6 years (13,15) at FDV.…”
Section: Discussioncontrasting
confidence: 81%
See 1 more Smart Citation
“…In the present study, only 0.6% of the children were under 1 year of age. An FDV at less than 3 years of age was reported in 3.00-40.50% of the population in previous studies (13,(19)(20)(21), whereas the rate was 5.5% in the present study. Other reports have stated that most of the children were aged between 6 and 9 years (12,19) or 3 and 6 years (13,15) at FDV.…”
Section: Discussioncontrasting
confidence: 81%
“…Studies reporting dental caries as the most common cause reported that 34.9-59.9% of the FDVs were due to caries (13,18,21). Studies reporting tooth pain as the most common cause reported that 33.1-34.9% of the FDVs were due to pain (12,14,15,20). These two reasons constituted 42.6-61.1% of the reasons for the FDV (12,14,15,20,21).…”
Section: Discussionmentioning
confidence: 99%
“…It is really astonishing to know that in various previous researches[ 19 20 ] carried out in other parts of the world, the age of 7–11 years and 6–12 years was being reported as the age for the first dental visit for their children. In a yet another study conducted in Bulgaria, the researchers noted that the study participants did not take their children to dentist earlier of the age of 1 year and they only visited the dentist in case their children suffered from dental caries or its complication.…”
Section: Discussionmentioning
confidence: 99%
“…These results were in accordance with previous studies, wherein the main reasons of children's first dental visit were pain and dental caries. [ 19 27 ]…”
Section: Discussionmentioning
confidence: 99%
“…In the present pioneer study among the dental students, 78.7% of them had had a visit to a dentist (Table 1), with only 2.6% visiting the dentist at an early age, i.e., 0 to 5 years, and 44.4% (188 out of 423) visited the dentist only after joining the dental college when they were older than 17 years of age (Table 2), thus exhibiting low awareness among the study population. Considering other studies carried by Meera et al, 8 which estimated the age of first dental visit to be more than 6 years, Ghimire 9 found it to be in the age group of 7 to 11 years, and Atulkar et al 10 reported that most of the subjects enrolled in their study had not visited the dentist until 17 years of age. It was found that the most common reason for visiting the dentist was caries followed by routine dental checkup, irregular teeth, and tooth pain, for various other reasons, fracture/trauma, and ulcers in the oral cavity ( Table 3), indicating that the visits were for interception rather than prevention of diseases.…”
Section: Discussionmentioning
confidence: 99%